The influence of human resource management on employee engagement in China coalmine industry - Xibei, Zhang (2019)
In the current competitive environment, a highly engaged employee team is an important factor for enterprise to obtain competitive advantage. The influence of employee engagement on organizational success is gradually recognized and has become a hot topic for industry to pay attention to human resource management practice. This study examined the human resource management (HRM) factors that influence employee engagement at Hongliu coalmine which consist of employee engagement, training and development, compensation and benefit as well as safety and health. The data were collected using survey to 300 employees of Hongliu coalmine in China and were utilized using SPSS version 25. The correlation analysis shows that training and development, compensation and benefit, and safety and health have positive correlation with employee engagement. The regression results positive influence between training and development, compensation and benefit, safety and health on employee engagement. Thus, implication of the results and future research on HRM practices are also discussed.